2014
DOI: 10.1186/cc13938
|View full text |Cite
|
Sign up to set email alerts
|

Beta-lactam dosing in critically ill patients with septic shock and continuous renal replacement therapy

Abstract: Although early and appropriate antibiotic therapy remains the most important intervention for successful treatment of septic shock, data guiding optimization of beta-lactam prescription in critically ill patients prescribed with continuous renal replacement therapy (CRRT) are still limited. Being small hydrophilic molecules, beta-lactams are likely to be cleared by CRRT to a significant extent. As a result, additional variability may be introduced to the per se variable antibiotic concentrations in critically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 54 publications
3
54
2
3
Order By: Relevance
“…In general, antibiotic dose adjustments in critically ill patients are very challenging for the clinician because, unlike other drugs, such as vasopressors or sedatives, among others, the pharmacological effect of antibiotics is not immediately evident but requires a certain period of time, even days, to be visible. For critically ill patients with septic shock and a CRRT requirement, detection of the pharmacological effect of antibiotics is even more challenging due to all the PK changes driven by critical illness and the use of extracorporeal devices (6). In spite of this difficulty, the attainment and maintenance of therapeutic concentrations are crucial, as they have an impact on both clinical outcomes and the development of bacterial resistances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, antibiotic dose adjustments in critically ill patients are very challenging for the clinician because, unlike other drugs, such as vasopressors or sedatives, among others, the pharmacological effect of antibiotics is not immediately evident but requires a certain period of time, even days, to be visible. For critically ill patients with septic shock and a CRRT requirement, detection of the pharmacological effect of antibiotics is even more challenging due to all the PK changes driven by critical illness and the use of extracorporeal devices (6). In spite of this difficulty, the attainment and maintenance of therapeutic concentrations are crucial, as they have an impact on both clinical outcomes and the development of bacterial resistances.…”
Section: Discussionmentioning
confidence: 99%
“…For these patients, available guidelines recommend that 500 to 1,000 mg of meropenem every 8 h (q8h) to every 12 h (q12h) be prescribed (7), which is a considerably broad dose range. However, this population is subject to conditions that may significantly influence meropenem pharmacokinetics (PKs) and, consequently, modify the dosing requirements, such as hypoproteinemia, variable urine output, or diverse CRRT settings (6). It follows that while several studies have described meropenem PKs in critically ill patients with continuous venovenous hemofiltration (CVVHF) and continuous venovenous hemodiafiltration (CVVHDF) (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), empirical dosing at the bedside is still challenging in this scenario.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Khawcharoenporn et al showed that combination therapy of nebulized colistin and carbapenems was an effective treatment option if carbapenems were given in a prolonged infusion fashion (37). In addition, previous studies indicated that individualized dosing of β-lactam antibiotics should be considered to increase the likelihood of optimal outcomes because of altered pharmacokinetics of β-lactam in critically ill patients (38,39). Because all patients in this study treated with colistin-carbapenem combination therapy received standard dosage regimen for carbapenems with intermittent bolus dosing, the unexpectedly low efficacy of colistincarbapenem combination might occur.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients, presenting dysfunction in vital organs such as kidney and liver that represent the major routes for drug elimination, are at increased risk of the prompt onset of toxic drug concentration [12,23]. On the other hand, patients with augmented renal clearance [24] or prescribed with continuous renal therapy suffer from decreased levels of antibiotics necessary to achieve a positive clinical outcome [25]. It is evident that different antibiotics are differently affected by the pathophysiological changes encountered in ICU patients.…”
Section: Impact Of Pathophysiological Changes On the Antimicrobial Thmentioning
confidence: 99%